An updated management approach of Pompe disease patients with high-sustained anti-rhGAA IgG antibody titers: experience with bortezomib-based immunomodulation - Desai, Ankit K.; Shrivastava, Garima; Grant, Christina L.; Wang, Raymond Y.; Burt, Trevor D.; Kishnani, Priya S. (Frontiers in Immunology, 2024)
High sustained anti-rhGAA antibody titers (HSAT; ≥12,800) are directly linked to reduced efficacy of enzyme replacement therapy (ERT) and subsequent clinical deterioration in infantile-onset Pompe disease (IOPD). We have previously demonstrated the safety and effectiveness of a bortezomib-based immune-tolerance induction (ITI) regimen (bortezomib, rituximab, methotrexate, and IVIG) in eliminating HSAT. Here, we describe two IOPD cases (patients 6 and 8) who developed HSAT at 8 and 10 weeks on ERT despite transient low-dose methotrexate ITI administration in the ERT-naïve setting and were treated with a bortezomib-based ITI regimen, and we compare their courses to a series of six historical patients (patients 1-5, and 7) with a similar presentation who exemplify our evolving approach to treatment. In total, patients 6 and 8 received 16 and 8 doses of bortezomib (4 doses=1 cycle) respectively reducing titers from 25,600 to seronegative, but differences in the course of their therapy were instructive regarding the optimal approach to initial treatment of HSAT; specifically, patient 6 was treated initially with only a single course of bortezomib rescue therapy, while patient 8 received two back-to-back courses. Patient 6 had a transient reduction in anti-rhGAA antibodies, after receiving a single initial cycle of bortezomib, but had a recurrence of high anti-rhGAA antibody titer after 160 weeks that required 3 additional cycles of bortezomib to ultimately achieve tolerance. In contrast, patient 8 achieved tolerance after being given two consecutive cycles of bortezomib during their initial treatment and had B cell recovery by week 54. Since the reduction in anti-rhGAA antibodies, both patients are doing well clinically, and have decreasing ALT, AST, and CK. No major infections leading to interruption of treatment were observed in either patient. The bortezomib-based ITI was safe and well tolerated. These case studies and our previous experience suggest that to achieve an effective reduction of HSAT, bortezomib should be initiated at the earliest sign of high anti-rhGAA antibodies with a minimum of two consecutive cycles as shown in patient 8. We recommend close monitoring of anti-rhGAA antibodies and early intervention with ITI as soon as significantly elevated anti-rhGAA antibody titers are noted.